Pendekatan Discovery Learning terhadap Motivasi Belajar Siswa Kelas V Sekolah Dasar (Studi Pada SD Negeri 2 Parakan Salam dan SDN 2 Sukajadi - Tri Sumartini; Erma Purwa Rahayu; Suharyanto H. Soro; Ida Tejawiani (Global Education Journal, 2026)
This study aims to determine the effect of the Discovery Learning approach on students' learning motivation. This study uses quantitative research with an experimental approach. The research design used is Pre-Experimental Design with a One Group Pretest-Posttest Design model. The study population was all fifth-grade students at SD Negeri 2 Parakansalam and SD Negeri 2 Sukajadi with a total of 58 students. Data collection techniques include observation, learning motivation questionnaires, and documentation. The main research instrument was a 25-item learning motivation questionnaire using a Likert scale. The results of the study showed that there was an effect of increasing student learning motivation after the implementation of the Discovery Learning approach. At SD Negeri 2 Parakansalam, the average learning motivation score increased from 63.8 to 84.7. While at SD Negeri 2 Sukajadi, the average score increased from 62.9 to 83.5. The results of the hypothesis test showed that the calculated t value was greater than the t table, so H₀ was rejected and H₁ was accepted. This indicates that the Discovery Learning approach has a significant effect on students' learning motivation. This study concluded that the Discovery Learning approach is effective in increasing elementary school students' learning motivation.